2020
DOI: 10.1080/1331677x.2019.1693906
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency and sustainability of public service obligations on scheduled air services between Almeria and Seville

Abstract: The objective of this paper is to examine how the imposition of Public Service Obligations (PSO) on certain routes may affect the transportation sector, with a focus on aviation in the European Single Market. Thus, this research investigates how this form of public intervention can be useful to access adequeate transport system in remote and peripherical regions. Subsequently, this paper intends to display that the imposition of PSO on aviation routes should be considered as a unique mean of market interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…In this concern, the Directorate-General for Mobility and Transport (DG MOVE) on behalf of the Commission should strengthen monitoring tasks, even beyond the surveillance system towards a unified governance code for the PSO impositions and related tender processes. In the case of PSO contracts tendered so far in Spain, including that of the PSO considered in this study (118V2020), related procurement procedures have been carried out from a single electronic platform at the national level, and since 2018 all of them tendered under a full e-procurement process [39]. Nowadays, however, not all EU state members have awarded their PSO contracts by tendering from a state contracting platform, but through various regional platforms (i.e., France, Italy, and the Czech Republic), and some, even not publishing all tender documents (i.e., Lithuanian and Croatian).…”
Section: Discussionmentioning
confidence: 99%
“…In this concern, the Directorate-General for Mobility and Transport (DG MOVE) on behalf of the Commission should strengthen monitoring tasks, even beyond the surveillance system towards a unified governance code for the PSO impositions and related tender processes. In the case of PSO contracts tendered so far in Spain, including that of the PSO considered in this study (118V2020), related procurement procedures have been carried out from a single electronic platform at the national level, and since 2018 all of them tendered under a full e-procurement process [39]. Nowadays, however, not all EU state members have awarded their PSO contracts by tendering from a state contracting platform, but through various regional platforms (i.e., France, Italy, and the Czech Republic), and some, even not publishing all tender documents (i.e., Lithuanian and Croatian).…”
Section: Discussionmentioning
confidence: 99%
“…As seen both in Tables 3 and 4, it was the most significant public procurement process for the awarding of PSO services under type 3 within the Spanish domestic market, in terms of both the total volume awarded (EUR 28,349,124) and the total duration of the contracts (144 months), with up to a total of three tender procedures. In addition, the analysis of the efficiency and sustainability of this PSO route in an earlier paper showed that the imposition of a PSO on this route resulted in enhanced demand for air services, and specifically compensation from the procurement contract for regular air services [26]. As shown in Figure 1, since August 2014, scheduled air services have been guaranteed thanks to the succession of two fixed-term PSO contracts.…”
Section: Considerations On Findings About Public Tenders Relating To ...mentioning
confidence: 98%